Data literacy in undergraduate research: A case study from student poster competitions - Margaret Marchant; C. Jeffrey Belliston (IASSIST Quarterly, 2025)
At universities, research involving data is often regarded as the domain of graduate students and faculty. However, undergraduate students also work with data within the research process, and it can be a core experience to prepare them for future education and careers. Research products from undergraduate students can demonstrate the extent of their data literacy skills and understanding, which are becoming central to success in graduate studies and the world of work. Since a leading way for undergraduate students to share research is through posters, this paper examines undergraduate posters at Brigham Young University (BYU) in the context of data literacy skills. The paper defines data literacy and the importance of undergraduate students becoming data literate. This case study shares the BYU context for the undergraduate poster competitions and the resulting strengths and gaps in data literacy education followed by suggestions for supporting and encouraging undergraduate research and data literacy development beyond the traditional area of data analysis.